SECRECY PROVISIONS IN FINANCIAL DISCLOSURE REPORTS OF PUBLIC SERVANTS - Amer Abdul Hussein Abbas, Thamer Mohammed Rukhis, Huda Abbas Muhammad Ridha (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
At the economic and political levels, the issue of public service employee financial disclosure is an important and sensitive issue. Its value tends to be that it specifically impacts the public employee's personal freedoms. Subsequently, the great effects of administrative and financial corruption, behind which there is political corruption, which is the engine of the two previous forms. It has become important to balance the personal freedoms and security of the public servant's personal information and the duty of transparency and financial disclosure. Normally, this duty can only be accomplished by legal mechanisms.